Pengaruh Media Pembelajaran Interaktif Berbantuan Website Educaplay Terhadap Hasil Belajar Siswa Kelas IV SD - Sayyidah Devita Jamil Putri; Dya Ayu Agustina Putri; Nourma Oktavia Rini (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
The purpose of this study is to examine the effects of using interactive learning resources from the Educaplay website on the learning outcomes of fourth-grade SD Islam Sunan Giri students. The method used is quantitative experimentation with a quasi-experiment non-equivalent control group design. 52 students were divided into two groups by the researcher: the experimental group, which used interactive teaching materials, and the control group, which used traditional teaching methods. Data is collected through pretest and posttest, and then it is analyzed using uji T to test hypotheses. The study's findings show that the learning outcomes of the experimental and control groups varied significantly (p-value < 0,001), indicating that the use of interactive learning materials on the Educaplay website has a positive impact on students' learning outcomes